Mapping Internationalization on US Campuses - Brajkovic, Lucia; Matross Helms, Robin (International Higher Education, 2018)
This article summarizes the results of the American Council on Education’s (ACE) 2016 Mapping Internationalization on U.S. Campuses survey, and explores their implications. Conducted every five years, Mapping assesses the current state of internationalization at American colleges and universities, analyzes progress and trends over time, and identifies future priorities. The 2016 Mapping survey addressed the six key areas that comprise CIGE’s Model for Comprehensive Internationalization: articulated commitment; administrative structures and staffing; curriculum, cocurriculum, and learning outcomes; faculty policies and practices; student mobility; and collaboration and partnerships.